Ionic Liquids Thermophysical Properties and Applications - Sohel Murshed, S. M. (IntechOpen, 2021)
Because of their unique properties and fascinating features, ionic liquids have numerous potential applications in engineering, analytics, physical chemistry, electrochemistry, tribology, and biology. This book discusses the thermophysical properties and other features of these emerging liquids. It also presents different methods of their production, as well as examines their potential use as new lubricants or lubricant additives and in gas chromatography. In addition, the book provides an archeological, historical, and technological background of alkali and alkali-earth salts and hydroxides. The book is a useful resource for students, researchers, engineers, manufacturers, academicians, and professionals working in the field of ionic liquids for real-world applications.